Free Amino Acids in Pacu, Piaractus mesopotamicus, Eggs and Larvae - Portella, M. C. [UNESP]; Takata, R. [UNESP]; Leitão, N. J. [UNESP]; Menossi, O. C. [UNESP]; Kwasek, K.; Dabrowski, K. (Wiley, 2013)
Free amino acids (FAA) are used principally as substrate in protein synthesis and the source of energy in aerobic catabolism. In marine fish, embryo and larvae FAA are used to maintain body fluid osmolality during fish early development. However, there is essentially no information about FAA concentrations in early ontogeny of freshwater neotropical species in comparison to marine fishes. Therefore, the aim of this study was to evaluate the FAA concentrations in pacu, Piaractus mesopotamicus, eggs and larvae. Broodstock fish were induced to spawn and ovulated females were stripped of their eggs and immediately sampled for analysis. Larvae were sampled right after hatching (HL) and after the completion of the yolk-sac absorption (YSA). The wet weight of the HL and YSA larvae amounted to 0.5±0.1mg and 1.1±0.3mg, respectively. HL larvae showed higher levels of most of the indispensable amino acids (IAA) in comparison to eggs and YSA larvae. Exceptions were observed with His and Trp that showed higher or similar levels, respectively, in YSA larvae. The FAA Orn, Tau, Glu, Gln, Gly, and Tyr increased concentrations in both larval stages while that of Tau was found in higher concentration in all analyzed stages. Also, the concentrations of Asn, Ala, Pro, Ser, and Asp were higher in HL larvae. Both larval stages displayed a rise in total free IAA/total free DAA (dispensable amino acids) ratio. The authors conclude that the highest level of FAA in HL pacu larvae is indicative of active proteolysis of yolk reserves and a probable catabolism regulation of some FAA through spare-effect. In addition, Tau is one of the major FAA occurring during pacu ontogeny and may be performing regulation on body fluid osmolality regulation. © Copyright by the World Aquaculture Society 2013.
Keywords: amino acid; bioaccumulation; body fluid; catabolism; embryonic development; finfish; larval development; ontogeny; oxic conditions; protein